2006
DOI: 10.1515/epoly.2006.6.1.347
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereospecific Polymerizations of 1,3-Butadiene with Cobalt(II) Pyridyl Bis(imine) Complexes

Abstract: A series of prototypical Co(II)-based pyridyl bis(imine) complexes {[2-(ArN=C(Me)) 2 C 5 H 3 N]CoCl 2 } (Ar = 2,6-C 6 H 3 Me 2 , 2,5-C 6 H 3 Me 2 , 2,4-C 6 H 3 Me 2 , 2,3-C 6 H 3 Me 2 ) bearing two methyl substituents on each imine aryl group are studied as precatalysts for the homopolymerization of 1,3-butadiene. They showed very high polymerization activities associated with ethylaluminum sesquichloride (EAS) as a cocatalyst. The Co(II) catalysts containing less hindered pyridyl bis(imine) ligands, say [2-(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Highly cis -1,4-polybutadienes (∼95%) were obtained with catalysts based on bidentate phosphine Co complexes (CoCl 2 [R 2 P­(CH 2 ) n PR 2 ]–MAO; R = Me, Et, Ph; n = 1, 2), independently of the type of bidentate phosphine ligand bonded to the cobalt atom. ,, Predominantly cis -1,4-polybutadienes were also recently obtained with several new catalytic systems based on cobalt complexes with bi- and tridentate ligands containing N and/or O as donor atoms (e.g., bis-imines, bis-imino-pyridines, keto-imines, and keto-pyridinimines), regardless of the nature of the ligand coordinated to the cobalt atom. ,,,, …”
Section: Catalysts Based On Transition Metal and Lanthanide Complexes...mentioning
confidence: 98%
See 2 more Smart Citations
“…Highly cis -1,4-polybutadienes (∼95%) were obtained with catalysts based on bidentate phosphine Co complexes (CoCl 2 [R 2 P­(CH 2 ) n PR 2 ]–MAO; R = Me, Et, Ph; n = 1, 2), independently of the type of bidentate phosphine ligand bonded to the cobalt atom. ,, Predominantly cis -1,4-polybutadienes were also recently obtained with several new catalytic systems based on cobalt complexes with bi- and tridentate ligands containing N and/or O as donor atoms (e.g., bis-imines, bis-imino-pyridines, keto-imines, and keto-pyridinimines), regardless of the nature of the ligand coordinated to the cobalt atom. ,,,, …”
Section: Catalysts Based On Transition Metal and Lanthanide Complexes...mentioning
confidence: 98%
“…89,91,115,116,161−191 Kim et al reported on the polymerization of 1,3-butadiene with catalysts based on Co(II) pyridyl bis(imino) complexes, bearing two methyl substituents in different positions on each iminoaryl group, and ethylaluminum sesquichloride (EASC) as cocatalyst; these systems, and in particular those containing the less hindered pyridyl bis(imino) ligands, were found to be very active, yielding high molecular weight polymers with a cis-1,4 content up to 96.4%. 161 Catalysts exhibiting high activity and high cis selectivity (cis-1,4 content up to 96.9%) were obtained by combining (salen)Co(II) complexes with MAO. The activity was strongly affected by the ligand structure of the (salen)Co(II) complexes, while the selectivity was only slightly influenced 162 (Figure 32).…”
Section: Catalysts Based On Transition Metal and Lanthanide Complexes...mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Cis-1,4 polybutadiene can be also co-polymerized, blended or terminally functionalized to prepare materials with unique mechanical or chemical properties such as styrene-butadiene rubber (SBR), high impact polystyrene (HIPS), acrylonitrile-butadiene-styrene (ABS) or hydroxyl terminated polybutadiene (HTPB). 4 Since the pioneer research launched by Natta, various rare earth metals and transition metal catalyst recipes have been considerably developed for initiating the cis-1,4 polymerization, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and the Ziegler-Natta type of catalytic systems of TiCl 4 /I 2 /Al(i-Bu) 3 , 23 CoCl 2 /pyridine/AlEt 2 Cl, 24,25 Ni(OOCR) 2 /BF 3 •OEt 2 /AlEt 3 , 26,27 and Nd (OOCR) 3 /EASC/Al(i-Bu) 2 H 28 have realized cis-1,4-polybutadiene on a large industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…A surprising finding of such ligand set in olefin polymerization may also be extrapolated to the area of conjugated diene polymerization. Reports on transition metals bearing such kind of ligands for butadiene polymerization, however, have only started to emerge in the literature [1, 14,15,58]. We have reported 2,6-bis(imino)pyridyl ligands ligated transition complexes for selectivity-controlled polymerization of butadiene [59], finding the selectivity can be tuned within a wide range from high cis-1,4 (97.0%) to high trans-1,4 (95.4%) just by altering the metal center.…”
Section: Introductionmentioning
confidence: 99%